Trajectory and perspectives of the Academic League of Gynecology and Obstetrics of Espirito Santo: Report of students and teachers coordinators of the project - Ribeiro Lima, Gustavo; Maciel da Silva Brito, Georgia; Kneipp Costa Rossi, Kárin; Musso Ribeiro de Oliveira Souza, Chiara (Guará Journal, 2018)
This article consists of an experience report on the participation and performance of volunteer coordinators and students of the LIGOES Extension Project - Academic League of Gynecology and Obstetrics of the State of Espírito Santo, working in the area of Gynecology and Obstetrics of the Hospital Universitário Cassiano Antônio Moraes (HUCAM ). This project provides the students of the medical undergraduate courses theoretical-practical knowledge related to the area of action, through the development of internal and external activities, encouraging multidisciplinarity in health. The adopted methodology aims at the learning and the humanization of the academic in relation to the patients of the Service of Gynecology and Obstetrics of HUCAM. Taking into account the entire history of the League and its perspectives, we can see how important the student’s contact with the community is for a more humanized and complete medical education.